1997
DOI: 10.1046/j.1468-2982.1997.1707765.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache During Pregnancy

Abstract: A questionnaire was submitted to 430 women 3 days after delivery, asking mainly about features of headache before and during pregnancy, and their possible modification or recurrence; moreover, delivery modalities and the condition of the newborn were evaluated. One-hundred-and-twenty-six (29.3%) were found to be primary headache sufferers (IHS criteria, 1988), 81 of whom had migraine without aura (MO), 12 migraine with aura (MA), and 33 tension-type headache (TH). In all three groups, about 80% showed complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
122
3
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 8 publications
11
122
3
4
Order By: Relevance
“…Similar to our findings, others have also found that a history of previous headaches is a significant risk factor for the development of postpartum headaches. 7,8,10 Stein et al 8 and Maggioni et al 12 also found an increased incidence in multiparous women. Perhaps one explanation is that multiparous women have more complicated lives after delivery as compared to primiparous women.…”
Section: Discussionmentioning
confidence: 92%
“…Similar to our findings, others have also found that a history of previous headaches is a significant risk factor for the development of postpartum headaches. 7,8,10 Stein et al 8 and Maggioni et al 12 also found an increased incidence in multiparous women. Perhaps one explanation is that multiparous women have more complicated lives after delivery as compared to primiparous women.…”
Section: Discussionmentioning
confidence: 92%
“…However, it is not obvious a priori that there is a bias related to migraine in GA distribution of births, and the few previous studies to investigate outcome of pregnancy in woman with migraine did not consistently find more preterm labor or low birth weights. 8,36,37 Other important limitations are the low observed prevalence of migraine (perhaps suggesting it is active or severe migraine that is reported), the lack of medical documentation and classification, and lack of information on migraine subtype, severity, frequency or recency; and no information on medications use or on whether there was associated placental pathology. We report the observations in the hope that these shortcomings will be rectified in a future study designed to investigate this association.…”
Section: Complex Web Of Interactionsmentioning
confidence: 99%
“…1 The prevalence of headaches during pregnancy has been reported to be as high as 35%. 2 Although most headaches are unrelated to an intracranial pathologic lesion, some headaches may herald ominous diagnoses, including eclampsia, stroke, tumor, subarachnoid hemorrhage, or cerebral venous thrombosis. Emergent evaluation of headache in the pregnant patient requires rational selection of acute neuroimaging studies, yet guidelines do not exist.…”
mentioning
confidence: 99%